Prevalence of antecedent Kawasaki disease in young adults with suspected acute coronary syndrome in high incidence cohort - Shyu, Tsung-Cheng; Wu, Chiung-Jen; Fu, Yun-Ching; Peng, Yi-Chin; Chuang, Tzu-Yao; Kuo, Ho-Chang; Hsieh, Kai-Sheng; Tai, I-Hsin (Frontiers in Cardiovascular Medicine, 2023)
Background Acute coronary syndrome (ACS) in early adulthood (<40 years old) may be associated with unrevealed diagnoses of Kawasaki disease (KD) in childhood. Daniels et al. showed that 5% of young adults with acute coronary syndrome might have antecedent Kawasaki disease in a cohort with Kawasaki disease incidence rates ranging from about 9 to 20 per 100,000 children under 5 years of age. However, there is no relevant research from the cohort with higher incidence rates (>80–100 per 100,000 children under 5 years of age) of Kawasaki disease. Methods We conducted a multicenter, retrospective study by reviewing medical records and angiographic data from two institutions (middle and southern Taiwan, respectively) of adults <40 years of age who underwent coronary angiography for clinically suspected acute coronary syndrome (2009–2019). Angiographic images were independently analyzed by three cardiologists who were blinded to the medical records. Demographic and laboratory data and risk factors of coronary artery disease were integrated to assess the likelihood of antecedent KD. Results All 323 young adults underwent coronary angiography, and 27 had coronary aneurysms. The patients’ clinical and angiographic characteristics were evaluated, and 7.4% had aneurysms likely to be associated with KD. Most subjects were male (23/24), and their low-density lipoprotein (LDL) levels were significantly higher (p = 0.028) than those of subjects unlikely to have KD. Conclusion This study proposed that the cohort with higher Kawasaki disease incidence rates may have a higher prevalence of young adult ACS associated with antecedent KD. The importance of determining the clinical therapeutic significance of antecedent Kawasaki disease in young adult ACS warrants advanced research. Higher LDL levels may have a long-term cardiovascular impact in KD patients with persistent coronary aneurysms.